Integration of Local Wisdom in Science Learning: Project-Based Additive Substance E-Module to Improve Science Literacy - Wiwin Wiwin; Bibin Rubini; Irvan Permana; Indriyani Rachman; Yayoi Kodama (Jurnal Pemberdayaan Masyarakat, 2025)
This study aims to develop an e-module for learning about additives in Natural Sciences, incorporating project-based learning and local wisdom to enhance the scientific literacy of Grade VIII junior high school students. The method employed is Research and Development (RD) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involved 32 students from SMPN 2 Padarincang. The module validation was conducted by material and media experts, as well as science teachers, using the Content Validity Ratio (CVR) and Content Validity Index (CVI), both of which indicated that the module is highly feasible and valid. A one-group pretest-posttest experimental design was used for the module trial, demonstrating a significant improvement in students' scientific literacy with an average N-gain value of 0.6421 (moderate category). The integration of local wisdom through the context of milkfish satay processing offers a relevant and engaging learning experience, promoting a deeper understanding of the concept of additives. Students responded positively to the e-module, providing strong feedback on its effectiveness. This research contributes to science education by offering an innovative, culturally relevant approach to teaching natural sciences, fostering improved scientific literacy, and illustrating the potential of project-based learning integrated with local wisdom. The findings suggest that project-based e-modules, when combined with local context, can be effective tools for enhancing scientific literacy in middle school students, advancing both pedagogical strategies and educational outcomes in science.